The Interplay Between Autophagy and RNA Homeostasis: Implications for Amyotrophic Lateral Sclerosis and Frontotemporal Dementia - Houghton, O. H.; Mizielinska, S.; Gomez-Suaga, P. (Frontiers in Cell and Developmental Biology, 2022)
Amyotrophic lateral sclerosis and frontotemporal dementia are neurodegenerative disorders that lie on a disease spectrum, sharing genetic causes and pathology, and both without effective therapeutics. Two pathways that have been shown to play major roles in disease pathogenesis are autophagy and RNA homeostasis. Intriguingly, there is an increasing body of evidence suggesting a critical interplay between these pathways. Autophagy is a multi-stage process for bulk and selective clearance of malfunctional cellular components, with many layers of regulation. Although the majority of autophagy research focuses on protein degradation, it can also mediate RNA catabolism. ALS/FTD-associated proteins are involved in many stages of autophagy and autophagy-mediated RNA degradation, particularly converging on the clearance of persistent pathological stress granules. In this review, we will summarise the progress in understanding the autophagy-RNA homeostasis interplay and how that knowledge contributes to our understanding of the pathobiology of ALS/FTD.